Determining the presence of Toxocara spp. and other soil-transmitted helminth eggs in soil samples of selected public open spaces in the University of the Philippines, Diliman and Barangay U>P. Campus - Beltran, Andrea Lois M.; Bernal, Alyana Ysabel M.; Cruz, Ma. Kathrina Cassandra C.; Dinong, Wynonah Maurie M.; Mistica, Myra S. (Manila College of Public Health, University of the Philippines Manila, 2024)
Soil-transmitted helminths (STH), which are classified as neglected tropical diseases attributed to poor sanitation and hygiene practices, remain highly prevalent in the Philippines despite STH combat programs. This includes Toxocara spp., which can be acquired through dogs' and cats' feces that can contaminate soil. With the increasing number of dogs and stray cats in urban areas, such as the UP Diliman, there have been still limited studies on soil contamination in such areas. Therefore, this study aims to determine the presence of Toxocara spp. and other soil-transmitted helminth eggs from selected public open spaces in UP Diliman and Barangay UP Campus. A total of 50 soil samples from 10 selected public open spaces were collected and processed using the sucrose flotation method. This study found an overall proportion of 16% for soil transmitted helminth eggs across the soil samples. Ascaris spp. and Toxocara spp. were the predominant helminths that accounted for 8% and 6% of the total soil samples, respectively. Furthermore, the prevalence of STH contamination was highest in the strata for residential areas (6%), while specific sampling sites at the Lagoon and Area 17 accounted for a proportion of 4% each. Consequently, the presence of STH eggs was influenced by the type and morphology of the eggs and several environmental conditions. The results provide evidence of soil contamination with STH eggs, including the zoonotic Toxocara, in public open spaces and residential areas within an urban area in the Philippines, with residential areas being the most contaminated. This suggests a persistent cycle of infection linking humans, animals, and the environment, highlighting the need for appropriate measures such as implementing a community-centered health education program to improve environmental sanitation and basic hygiene.
Includes references and appendices.
Special Study
Keywords: University of the Philippines, Diliman -- Environmental conditions; Toxocara -- Philippines -- Quezon City; Soil-transmitted helminthiasis -- Transmission -- Philippines -- Quezon City; Soil pollution -- Environmental aspects -- Philippines -- Quezon City; Quezon City (Philippines) -- Public spaces -- Health aspects